(untitled) (Research, Society and Development, 2021)
This study analyzes the clinical, macroscopic and radiographic characteristics of a biomaterial with different proportions of wolastonite (W) and tricalcium phosphate (TCP) on bone tissue regeneration during the implantation process of an experimental model of critical bone defects. Fifteen Wistar rats were used, randomly distributed in 5 groups (n = 3), with a bone defect created on an 8.0 mm diameter calvaria. 4 groups received implants with different proportions of W%/TCP%, referred to as W20/TCP80, W40/TCP60, W60/TCP40 and W80/TCP20. The fifth control group (GC) was filled with blood clot only. Clinical evaluation was performed every 24 hours, and after 7 days, the animals were euthanized. The calvaria were dissected and analyzed macroscopically and by radiography. All study groups showed a satisfactory clinical evolution. The macroscopic analysis showed filling of the bone defect with granules surrounded by newly formed tissue, and the radiographic analysis showed different patterns of displacement of the biomaterial. The study concluded that the different proportions of W%/TCP% were well tolerated by the study groups and demonstrated biocompatibility. The enhanced hydrophilic behavior of the W40/TCP60, W60/TCP40 and W80/TCP20 groups favored the application in the experimental model in vivo.